Investigação química de Dictyoloma vandellianum: avaliação do perfil químico e do potencial antibacteriano frente a Xanthomonas citri subsp. citri - Borges, Karen Moraes (2025)
Dictyoloma vandellianum is a species of the Rutaceae family known for its diversity of secondary metabolites with biological potential. This study aimed to characterize compounds present in leaf extracts of the plant, focusing on the prospecting of substances with potential antibacterial activity against Xanthomonas citri subsp. citri, the causal agent of citrus canker. Crude extracts were obtained using solvents of different polarities and subsequently analyzed by HPLC-PDA to assess the chromatographic profile. A detailed analysis of the constituents was carried out by UHPLC-QTOF-MS/MS in both ionization modes, followed by data processing using metabolomics platforms (MS-DIAL, MS-FINDER, and GNPS), with in silico annotation and molecular networking. This approach revealed the presence of compounds belonging to the classes of flavonoids, alkaloids, quinolones, and coumarins. Three substances were isolated through chromatographic fractionation and structurally characterized by one- and two-dimensional NMR spectroscopy, with validation based on fragmentation patterns observed in mass spectrometry. Although the identified structures are not novel, they were confirmed with a high level of confidence using the employed analytical methods. The results reinforce the potential of D. vandellianum as a source of bioactive metabolites and provide a solid foundation for future investigations. Next steps include testing the isolated compounds against the phytopathogen and structural characterization of additional constituents yet to be identified.